2017
DOI: 10.1002/ijc.30587
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor air pollution and risk for kidney parenchyma cancer in 14 European cohorts

Abstract: Several studies have indicated weakly increased risk for kidney cancer among occupational groups exposed to gasoline vapors, engine exhaust, polycyclic aromatic hydrocarbons and other air pollutants, although not consistently. It was the aim to investigate possible associations between outdoor air pollution at the residence and the incidence of kidney parenchyma cancer in the general population. We used data from 14 European cohorts from the ESCAPE study. We geocoded and assessed air pollution concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 36 publications
(90 reference statements)
0
31
0
2
Order By: Relevance
“…The consistency of the HRs between the cohorts indicates that the association between PM 2.5 and gastric cancer is no chance finding. Further support for an association between PM 2.5 and cancer risk comes from other ESCAPE studies, in which PM 2.5 together with PM 10 was the pollutant that was most clearly and strongly associated with increased risks of lung and kidney cancer …”
Section: Discussionmentioning
confidence: 99%
“…The consistency of the HRs between the cohorts indicates that the association between PM 2.5 and gastric cancer is no chance finding. Further support for an association between PM 2.5 and cancer risk comes from other ESCAPE studies, in which PM 2.5 together with PM 10 was the pollutant that was most clearly and strongly associated with increased risks of lung and kidney cancer …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in China has shown that long-term exposure to PM 2.5 is associated with an increased risk of membranous nephropathy [ 6 ]. Furthermore, some studies have demonstrated that long-term exposure to outdoor PM can increase the risk of kidney parenchyma cancer [ 7 , 8 ]. Lately, Aztatzi-Aguilar et al demonstrated that subchronic exposure to PM 2.5 induced an acute kidney damage that involved an angiotensin and bradykinin system as well as antioxidant and immune imbalance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Même si le rôle de la pollution atmosphérique dans l'étiologie des maladies respiratoires chroniques est encore un sujet de débat, de nombreuses études épidémiologiques ont mis en évidence des liens entre maladies cardio-respiratoires et pollution atmosphérique, notamment par des particules fines d'origine chimique ou organique [1] [3]. L'exposition, même à court terme (pic de pollution) ou chronique, à la pollution atmosphérique semble être associée aux troubles asthmatiques [4], au cancer du poumon [5] et du rein [6], à l'infarctus du myocarde [7], aux perturbations de la fonction thyroïdienne [8], à la croissance des cellules épithéliales bronchiques [9] et à l'augmentation de la mortalité cardiovasculaire [10]. Selon l'Organisation mondiale de la santé, la pollution atmosphérique cause chaque année en moyenne la mort prématurée d'environ six millions de personnes dans le monde [11].…”
Section: Transports En Commun Pollution Et Défis Sanitaires Associésunclassified